Shallow Groundwater Quality Assessment in Muang District, Phayao - Rangsayatorn, Niramol (Asian Health, Science and Technology Reports, 2006)
A shallow groundwater well is the important source of potable water for the remote area. This study aimed to improve the state of knowledge on the quality of shallow groundwater in Muang District, Phayao Province. Thirty five shallow groundwater wells were sampled for the water quality testing. Inorganic contents (NO3, As, Cd, Cu, Pb, F, Fe, Mn and Zn) and microbiological contamination, using fecal coliform bacteria as indicators, were investigated. The shallow well maintenance and locations were also studied. Although, 3 of 8 analyzed metals (F, Fe and Zn) were detected in shallow groundwater, the concentrations of those metals were within the standard norms proposed by the Pollution Control Department of Thailand. In contrast to the metal content, the nitrate concentrations were higher than standard (> 45 mg/l). Water hardness was between 60.89-1656.50 mg/l, and twenty one from thirty five samples were considered hard water. Coliform bacteria were found in all samples. This indicated that shallow wells had been contaminated with the fecal material of human beings or other animals. The cause of contamination could be that shallow wells were located very close to septic tanks. Moreover, the shallow wells were poorly maintained. The buckets and robes used to draw water in some wells were seen lying on the ground between uses and some wells were not covered.